B-IGEV (bortezomib plus IGEV) versus IGEV before high-dose chemotherapy followed by autologous stem cell transplantation in relapsed or refractory Hodgkin lymphoma: a randomized, phase II trial of the Fondazione Italiana Linfomi (FIL). Issue 10 (2nd October 2016) - Balzarotti, Monica; Brusamolino, Ercole; Angelucci, Emanuele; Carella, Angelo Michele; Vitolo, Umberto; Russo, Eleonora; Congiu, Angelagiovanna; Gotti, Manuel; Massidda, Stefania; Botto, Barbara; Annechini, Giorgia; Spina, Michele; et al.
Abstract: This randomized, multicenter study evaluates the addition of bortezomib (13 mg/m 2 ) to IGEV (B-IGEV) in patients with relapsed/refractory Hodgkin Lymphoma (HL). Patients received either four courses of IGEV alone ( n  = 40) or B-IGEV ( n  = 40). The primary endpoint was the complete response (CR) proportion, evaluated by FDG-PET, after induction chemotherapy. CR proportion was 39% with B-IGEV and 53% with IGEV. PFS and OS were similar between the two groups (two-year PFS: 58% vs 56%; two-year OS: 93% vs 81%). The PET-negative status after treatment was the only variable favorably influencing both PFS (two-year PFS: 77% vs 40%; p  = 0.002) and OS (two-year OS: 100% vs 76%; p  < 0.001). Toxicity was overall similar with the two regimens. The addition of bortezomib to IGEV does not improve response in relapsed/refractory HL patients. However, its favorable therapeutic and safety profile, and the prognostic role of pre-transplant PET negativity in patients receiving IGEV-based regimens are confirmed.